The Influence of ESG Performance on Cost of Debt : The Moderating Role of Agency Cost - Saputra, Mohan Maulana; Eka Pria Anas (Universitas Muhammadiyah Surakarta, 2025)
This study examines the relationship between ESG (Environmental, Social, and Governance) performance and the cost of debt, with agency cost as a moderating variable. Using panel data from companies listed on the Indonesia Stock Exchange (IDX) for the period 2018–2023, this research employs panel regression and interaction analysis. The results show that ESG performance has a positive and significant effect on the cost of debt, indicating that higher ESG scores may be associated with increased costs from the creditors’ perspective. Furthermore, agency cost negatively and significantly moderates this relationship, suggesting that when agency costs are high, the positive effect of ESG on the cost of debt is weakened. These findings imply that while ESG initiatives are often perceived as positive signals, their benefits in reducing debt costs may be limited when internal inefficiencies or managerial conflicts exist. The study contributes to the understanding of how internal governance factors interact with sustainability efforts in influencing corporate financing outcomes.